A Flipped Classroom Learning Model Based on Social and Emotional Learning to Improve the Pancasila Student Profile Values in Science and Environment Learning - Elpina; Yesi Anita; Ary Kiswanto Kenedi; Rafhi Febryan Putera; Hasmai Bungsu Ladiva; Nurul Qolbi; Atika Ulya Akmal (Jurnal Penelitian Pendidikan IPA, 2024)
This research is motivated by the low Pancasila student profile values in elementary school students, caused by suboptimal learning processes that need to facilitate active student interaction, provide more time for individualized approaches, support 21st-century skills, focus on character development, and leverage technology. Hence, there is a need to develop a learning model that addresses these aspects. This research aims to develop a flipped classroom learning model based on social and emotional learning that is valid and effective in improving the Pancasila student profile values in elementary school students. This research employs the ADDIE model for development and involves nine validators and 200 elementary school students. The research instruments include observation sheets, validation questionnaires, and Pancasila student profile questionnaires. Data analysis techniques include descriptive statistical analysis and T-test statistical analysis using the JAMOVI application. The results of this study demonstrate that the developed flipped classroom learning model based on social and emotional learning is valid and effective in improving the Pancasila student profile values in elementary school students. The implications of this research can serve as a foundation for developing and enhancing the Pancasila student profile values in elementary school students.